How health and well-being are experienced and conditioned in the daily school life of young people recently migrated to Sweden - Lögdberg, Ulrika (Halmstad University, 2023)
With the school as a point of departure, the dissertation’s overarching aim is to explore everyday experiences of and conditions for health and well-being among young people who recently migrated to Sweden. Further, the aim is to illuminate and problematize the conditions and circumstances within which health is created and negotiated for this group of youths. The newly arrived youths’ experiences and conditions for health and well-being are analyzed through an overall social and cultural framework that emphasizes everyday life and micro-processes. At the same time, everyday experiences, social positionings, and material conditions, explored in the various studies, are linked to power processes. The individual’s room for agency in daily life depends on historical, structural, and relational conditions. In other words, health is related to power in various ways, which forms an extensive part of the dissertation’s analytical focus. The empirical material (data) was created through three independent data collections with three different groups of participants. The study participants are males and females (16–20 years old) from Afghanistan, Syria, Somalia, Ethiopia, Burundi, Thailand, Turkmenistan, Palestine, Kosovo, and Greece*. The data collection took place in the spring of 2014 (Study I), between February and April 2016 (Study II), and between April and June 2017 (studies III & IV). A qualitative and health-promoting design was used in Study I comprising qualitative task-based interviews focusing on the health and well-being of young people. Photovoice, a participatory research method well-suited for youth participation, was used in Study II. An ethnographic approach was used in Study III and IV, including participant observations, qualitative semi-structured interviews, and more informal conversations documented through field notes.

This dissertation is based on the following scientific articles:
I. Lögdberg, U., Nilsson, B., & Kostenius, C. (2018). “Thinking about the future, what’s gonna happen?” – How young people in Sweden who neither work nor study perceive life experiences in relation to health and well-being. International Journal of Qualitative Studies on Health and Well-being, 13(1), 1–12.
II. Lögdberg, U., Nilsson, B., & Kostenius, C. (2020). Young Migrants’ Experiences and Conditions for Health: A Photovoice Study. SAGE Open, 10(2), 1–12.
III. Lögdberg, U., Öhlander, M., & Nilsson, B. (Submitted). Everyday navigation between adaptation and resistance: How young people negotiate their well-being in relation to assigned migrant positions in school.
IV. Lögdberg, U., Öhlander, M., Lindgren, E-C., & Nilsson, B. (Submitted). Social, spatial, and material conditions for mattering: Newly arrived young migrants’ possibilities to matter in everyday life in a Swedish school.

*Participants in Study I comprised 16 young people aged 16–20. Eight were born in Sweden, and eight had immigrated to Sweden in the past couple of years. The dissertation focuses on the newly arrived youths’ perspectives. The eight participants born in Sweden are not counted as participants in the comprehensive summary. However, in Study I, all participants’ perspectives are included in the published article (Study I).

1. A PDF file with Interview transcripts from 18 interviews
2. 16 PDF files with timelines as part of task-based interviews
3. A PDF file with 86 images with associated text taken individually by the participants as well as transcripts from group interviews.
4. A PDF file with field notes from observations and conversations with participants.
5. A PDF file with interview transcripts from six interviews.

Med fokus på det dagliga livet i skolan är avhandlingens övergripande syfte att utforska vardagliga erfarenheter av, förutsättningar för samt villkorande av hälsa och välbefinnande bland unga personer som nyligen migrerat till Sverige, samt att utforska hur detta kan förstås i termer av vardagens sociala och kulturella processer. Härigenom belyser och problematiserar avhandlingen de förutsättningar och omständigheter inom vilka hälsa skapas och förhandlas för denna grupp unga. De sociala och kulturella processerna, som utgör de nyanlända ungdomarnas förutsättningar för hälsa och välmående, analyseras så som de kommer till uttryck i vardagslivet och som mikroprocesser. Samtidigt är vardag, dess sociala interaktion, sociala positioneringar och materiella villkor för välmående, som utforskas i de olika studierna, kopplade till mer övergripande maktprocesser. Individens handlingsutrymme i det dagliga livet förstås som beroende av politiska, strukturella och relationella förhållanden. Hälsa är med andra ord relaterat till makt på olika sätt, vilket utgör en omfattande del av avhandlingens analytiska fokus. Empiriskt baseras avhandlingen på tre oberoende datainsamlingar. Datainsamlingen liksom analysen bygger på ett kvalitativt, explorativt och hälsofrämjande förhållningssätt. Deltagarna i studierna är män och kvinnor, 16–20 år, från Afghanistan, Syrien, Somalia, Etiopien, Burundi, Thailand, Turkmenistan, Palestina, Kosovo och Grekland*. Datainsamlingen skedde under våren 2014 (Studie I), mellan februari och april 2016 (Studie II) och mellan april och juni 2017 (studier III & IV). En kvalitativ och hälsofrämjande design användes i Studie I bestående av kvalitativa uppgiftsbaserade intervjuer med fokus på ungas hälsa och välbefinnande. Photovoice, en forskningsmetod väl lämpad för ungdomars deltagande, användes i studie II. Ett etnografiskt tillvägagångssätt som inkluderade deltagande observationer, kvalitativa semistrukturerade intervjuer och mer informella samtal dokumenterade genom fältanteckningar, användes i Studie III och IV.

Avhandling bygger på följande vetenskapliga artiklar:
I. Lögdberg, U., Nilsson, B., & Kostenius, C. (2018). “Thinking about the future, what’s gonna happen?” – How young people in Sweden who neither work nor study perceive life experiences in relation to health and well-being. International Journal of Qualitative Studies on Health and Well-being, 13(1), 1–12.
II. Lögdberg, U., Nilsson, B., & Kostenius, C. (2020). Young Migrants’ Experiences and Conditions for Health: A Photovoice Study. SAGE Open, 10(2), 1–12.
III. Lögdberg, U., Öhlander, M., & Nilsson, B. (Submitted). Everyday navigation between adaptation and resistance: How young people negotiate their well-being in relation to assigned migrant positions in school.
IV. Lögdberg, U., Öhlander, M., Lindgren, E-C., & Nilsson, B. (Submitted). Social, spatial, and material conditions for mattering: Newly arrived young migrants’ possibilities to matter in everyday life in a Swedish school.

*Deltagare i Studie I bestod av 16 ungdomar i åldern 16–20 år. Åtta är födda i Sverige och åtta hade invandrat till Sverige under de senaste åren. Avhandlingen fokuserar på de nyanlända ungdomarnas perspektiv. De åtta deltagarna födda i Sverige räknas inte som deltagare i avhandlingen. I Studie I ingår dock alla deltagares perspektiv i den publicerade artikeln (Studie I).

1. En PDF-fil med Intervjutranskript från 18 intervjuer
2. 16 PDF-filer med tidslinjer som en del av uppgiftsbaserade intervjuer
3. En PDF-fil med 86 bilder med tillhörande text tagna individuellt av deltagarna samt utskrifter från gruppintervjuer.
4. En PDF-fil med fältanteckningar från observationer och samtal med deltagare.
5. En PDF-fil med intervjutranskript från sex intervjuer.
Hur hälsa och välbefinnande upplevs och villkoras i skolans vardag för unga som nyligen migrerat till Sverige
Keywords: Emotions; Emotioner; Life Change Events; Livsavgörande händelser; Interpersonal Relations; Mellanmänskliga relationer; Social Support; Socialt stöd; Stress, Psychological; Psykologisk stress; Quality of Life; Livskvalitet; schools; skolor; social exclusion; social exklusion; ethnography; etnografi; Adolescent; Ungdomar; Attitude to Health; Attityder till hälsa; Emigration and Immigration; Utvandring och invandring; Social Isolation; Social isolering; Unemployment; Arbetslöshet; Vulnerable Populations; Sårbar befolkning; Qualitative Research; Kvalitativ forskning; Young Adult; Unga vuxna; Photovoice; Photovoice; Semi-structured interviews; Semistrukturerade intervjuer; Migration; Migration; General health and well-being; Allmän hälsa och välbefinnande; Other Health Sciences; Annan hälsovetenskap; Public health; Folkhälsa; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin